Validation of the EuroSCORE risk models in Turkish adult cardiac surgical population - Akar, Ahmet Ruchan; Kurtcephe, Murat; Sener, Erol; Alhan, Cem; Durdu, Serkan; Kunt, Ayse Gul; Guvenir, Halil Altay; Cardiovasc, Working Grp Turkish Soc (OXFORD UNIV PRESS INC, 2011)
Objective: The aim of this study was to validate additive and logistic European System for Cardiac Operative Risk Evaluation (EuroSCORE) models on Turkish adult cardiac surgical population. Methods: TurkoSCORE project involves a reliable web-based database to build up Turkish risk stratification models. Current patient population consisted of 9443 adult patients who underwent cardiac surgery between 2005 and 2010. However, the additive and logistic EuroSCORE models were applied to only 8018 patients whose EuroSCORE determinants were complete. Observed and predicted mortalities were compared for low-, medium-, and high-risk groups. Results: The mean patient age was 59.5 years (+/- 12.1 years) at the time of surgery, and 28.6\% were female. There were significant differences (all p < 0.001) in the prevalence of recent myocardial infarction (23.5\% vs 9.7\%), moderate left ventricular function (29.9\% vs 25.6\%), unstable angina (9.8\% vs 8.0\%), chronic pulmonary disease (13.4\% vs 3.9\%), active endocarditis (3.2\% vs 1.1\%), critical preoperative state (9.0\% vs 4.1\%), surgery on thoracic aorta (3.7\% vs 2.4\%), extracardiac arteriopathy (8.6\% vs 11.3\%), previous cardiac surgery (4.1\% vs 7.3\%), and other than isolated coronary artery bypass graft (CABG

23.0\% vs 36.4\%) between Turkish and European cardiac surgical populations, respectively. For the entire cohort, actual hospital mortality was 1.96\% (n = 157

95\% confidence interval (CI), 1.70-2.32). However, additive predicted mortality was 2.98\% (p < 0.001 vs observed

95\% CI, 2.90-3.00), and logistic predicted mortality was 3.17\% (p < 0.001 vs observed

95\% CI, 3.03-3.21). The predictive performance of EuroSCORE models for the entire cohort was fair with 0.757 (95\% CI, 0.717-0.797) AUC value (area under the receiver operating characteristic, AUC) for additive EuroSCORE, and 0.760 (95\% CI, 0.721-0.800) AUC value for logistic EuroSCORE. Observed hospital mortality for isolated CABG was 1.23\% (n = 75

95\% CI, 0.95-1.51) while additive and logistic predicted mortalities were 2.87\% (95\% CI, 2.82-2.93) and 2.89\% (95\% CI, 2.80-2.98), respectively. AUC values for the isolated CABG subset were 0.768 (95\% CI, 0.707-0.830) and 0.766 (95\% CI, 0.705-0.828) for additive and logistic EuroSCORE models. Conclusion: The original EuroSCORE risk models overestimated mortality at all risk subgroups in Turkish population. Remodeling strategies for EuroSCORE or creation of a new model is warranted for future studies in Turkey. (C) 2011 European Association for Cardio-Thoracic Surgery. Published by Elsevier B.V. All rights reserved.
Keywords: Cardiac surgery; Risk prediction model; Mortality; EuroSCORE; TurkoSCORE